ADOPSI TEKNOLOGI DIGITAL OLEH LANSIA: HAMBATAN, PEMAKNAAN, DAN AKSES INFORMASI KESEHATAN - Syaza Yasmin (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2025)
This study aims to understand the experiences of older adults in adopting communication technology, particularly the use of smartphones and the internet, to obtain health information. It also examines their level of digital literacy in searching for and filtering health-related information through digital media. The study employs a qualitative approach using phenomenological methods and semi-structured interviews to explore the meanings and interpretations that older adults ascribe to their experiences with communication technology in accessing health information. The findings reveal that older adults strive to adopt and utilize communication technology, with WhatsApp and YouTube serving as their primary sources of health information. However, they encounter several challenges in adopting technology, including intrapersonal barriers (fear of technology), functional barriers (declining vision and motor skills), structural barriers (limited internet access), and interpersonal barriers (lack of social support). Additionally, older adults recognize the challenges of assessing the accuracy and credibility of health information, leading them to rely on family members or healthcare professionals at medical service centers. This study provides valuable insights into the process of technology adoption among older adults and their perception of digital technology as a medium for accessing health information.